EFEKTIVITAS PERAN DESA LEMBONGAN DALAM PENANGANAN PELANGGARAN PEMBANGUNAN DI SEMPADAN PANTAI DENGAN DAMPAK PENCEMARAN LINGKUNGAN - Jayswara, Kadek Aries; Sudiana, A.A Kt (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Lembongan Village, located in the coastal area of Nusa Penida District, Klungkung Regency, faces significant challenges in maintaining coastal environmental sustainability amid rapid tourism growth. This study focuses on the effectiveness of Lembongan Village's role in addressing coastal boundary violations that lead to environmental pollution. Using an empirical legal approach and analysis of local policies, this research evaluates the village's role in supervision, mediation, education, and law enforcement. The study's findings indicate that uncontrolled development, including the construction of villas, homestays, and restaurants, has significantly impacted marine ecosystem degradation and beach erosion. Despite efforts in law enforcement, the main challenges faced include a lack of community awareness, inconsistencies in law enforcement, and limited resources. This research recommends enhancing more comprehensive local regulations, sustainable environmental education, and collaboration between the village government and the community to create a more sustainable coastal environment. Thus, it is hoped that Lembongan Village can maintain environmental sustainability while supporting the welfare of the local community, which depends on coastal resources.